2021
DOI: 10.1186/s12864-021-07789-7
|View full text |Cite
|
Sign up to set email alerts
|

Modelling segmental duplications in the human genome

Abstract: Background Segmental duplications (SDs) are long DNA sequences that are repeated in a genome and have high sequence identity. In contrast to repetitive elements they are often unique and only sometimes have multiple copies in a genome. There are several well-studied mechanisms responsible for segmental duplications: non-allelic homologous recombination, non-homologous end joining and replication slippage. Such duplications play an important role in evolution, however, we do not have a full unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…This network approach allows studying segmental duplications as a whole thus revealing some universal biological principles of SDs evolution from the SD network. Earlier we observed that duplication rates grow with the number of copies of a specific duplicated region, which we called preferential duplication rates Abdullaev et al [2021]. This time we further examined the biological characteristics that could affect duplication rates.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This network approach allows studying segmental duplications as a whole thus revealing some universal biological principles of SDs evolution from the SD network. Earlier we observed that duplication rates grow with the number of copies of a specific duplicated region, which we called preferential duplication rates Abdullaev et al [2021]. This time we further examined the biological characteristics that could affect duplication rates.…”
Section: Discussionmentioning
confidence: 94%
“…We simulated the PCM network growth and kept information on edges status ("primary" edges representing duplication events or "secondary" ones). All PCM simulations were done with the parameters inferred at (Abdullaev et al [2021]): δ = 5.1 * 10 −4 , f = 0.47. We also considered other centrality measures assigned to nodes of the SD network (Table 2) and estimated an accuracy of each of them when applied to our task.…”
Section: Reconstruction Of Segmental Duplication Rates a Preprintmentioning
confidence: 99%
See 1 more Smart Citation
“…Afterwards, these duplicon blocks are copied to other pericentromeric sites, creating a mosaic structure [28]. Interchromosomal duplications are enriched in subtelomeric LCRs via serial translocations (Figure 2C): consecutive events of double-strand breakage and repair in these subtelomeric regions created a mosaic pattern of LCR-containing sequences [28,30]. The largest LCRs in the human genome, are located in interstitial regions and are enriched for intrachromosomal duplications.…”
Section: Distribution Origin and Evolution Of Lcrsmentioning
confidence: 99%
“…The complex patterns are formed by serial duplication, using the LCRs themselves as homology substrates in consecutive rounds (Figure 2D) [28,30]. Alu repeats are frequently observed at or in the vicinity of the boundaries of LCRs, suggesting involvement of both NAHR and replication-based mechanisms (NHEJ, MMBIR) in the creation of these complex structures [28][29][30][31]. The proportion of LCR sequence varies substantially between the genomes of different species.…”
Section: Distribution Origin and Evolution Of Lcrsmentioning
confidence: 99%